Message spaces for perfect correlated equilibria - CHATTERJI, Shurojit (Institutional Knowledge at Singapore Management University, 2006)
We show that a perfect correlated equilibrium distribution of an N-person game, as defined by Dhillon and Mertens (1996) can be achieved using a finite number of copies of the strategy space as the message space.